Primary Mapping and Analysis of the CmARM14 Candidate Gene for Mature Fruit Abscission in Melon - Dongyang Dai; Ling Wang; Junming Zhang; Haojie Qin; Huiying Liu; Yunyan Sheng (Agronomy, 2022)
Mature fruit abscission (MFA) is an important trait in terms of both harvest and yield. MFA can affect the production and economic value of melon fruit. An F3 population segregating for a single gene and derived from a cross between line M2-10, which shows no mature fruit abscission (None MFA), and the MFA line ZT00091 was used to map candidate genes. Specific length amplified fragment (SLAF) sequencing, in conjunction with bulked-segregant analysis (BSA), was used to map loci governing the natural fruit abscission of plants composing the F3-57 family. A candidate locus, mfa10.1, located on chromosome 10 between genomic positions 73,229 and 818,251, was obtained. An insertion-deletion (InDel) marker and 46 recombinant individuals were used to narrow the candidate region to within 35 kb at the genomic position of 650,203 to 685,250; this region included six candidate genes. qRT–PCR gene expression and gene sequence data showed that the CmARM14 gene, which encodes a RING-type E3 ubiquitin transferase (MELO3C012406), was a candidate for melon MFA. Subcellular localization observations revealed that the CmARM14 fusion protein was localized to the golgi apparatus. Taken together, these results provide a molecular basis for melon breeding.